RANCANG BANGUN APLIKASI AGROBISNIS MARKETPLACE BERBASIS LOKAL “AGRITION” AGRICULTURE SOLUTION - Ade Hendini; Yuza Fahrul Mujtahid (STMIK KAPUTAMA, 2020)
Food needs are very important, but how about if there is a food is difficult to find in the local market. Problems arise because of difficulties in finding stalls or other markets that have food or agricultural products to be sought. By looking back at the development of various types of marketplaces in this era, it would be very helpful to create a locally-based marketplace, which only displays food products in the surrounding area, so that it can provide opportunities for local farmers to market their products.